Trend and factors associated with multiple arterial revascularization in coronary artery bypass grafting in the UK. (2nd May 2022) - Chan, Jeremy; Dimagli, Arnaldo; Dong, Tim; Fudulu, Daniel P; Sinha, Shubhra; Angelini, Gianni D
Abstract: OBJECTIVES: Benefits of using multiple arterial grafting (MAG), over single arterial grafting in major adverse cardiac event rates and the need for repeat revascularization, have been widely reported. Several guidelines have recommended the use of MAG in selected patients. We report the trend of MAG in patients undergoing isolated coronary artery bypass grafting (CABG) in the UK. METHODS: This is a retrospective analysis of a prospectively collected UK national database in patients undergoing non-emergency, isolated CABG from 1996 to 2018. Patients were divided into single arterial grafting and MAG, and trends in perioperative characteristics were analysed. RESULTS: A total of 336 321 patients were included, of whom 284 003 (84.44%) received single arterial grafting and 52 318 (15.56%) received MAG. The use of MAG after an initial increase from 1996 to 2001, steadily decreased thereafter, particularly in the use of radial artery. MAG was likely to be performed in younger patients [66.72 (standard deviation: 9.22) vs 62.30 (standard deviation: 10.06), P < 0.001] and males (85% vs 81%, P < 0.001). After propensity score matching, the single arterial grafting group was more likely to undergo on-pump CABG (90% vs 69%, P < 0.001), experienced a lower in-hospital mortality (1.1% vs 1.3%, P < 0.001) and incidence of return to theatre for bleeding (2.5% vs 3.0%, P < 0.001). CONCLUSIONS: Our data show that the use of MAG in CABG in the UK after an initial increase from 1996 to 2001 steadily decreased thereafter until 2018. This is likely to be multifactorial and a better understanding of the main causes may contribute to establishing the best indication for MAG in everyday clinical practice. Abstract : Several prospective studies and randomized control trials reported the benefits of multiple arterial grafting (MAG), including a reduction in the need for repeat revascularization, major adverse cardiac events and new myocardial infarction, compared to single arterial grafting (SAG) [1].